Crystal structure of trans-diaqua(1,4,8,11-tetraazaundecane)nickel(II) bis(pyridine-2,6-dicarboxylato)nickel(II) - Irina L. Andriichuk (International Union of Crystallography, 2021)
The asymmetric unit of the title compound, trans-diaqua(1,4,8,11-tetraazaundecane-κ4N1,N4,N8,N11)nickel(II) bis(pyridine-2,6-dicarboxylato-κ3O2,N,O6)nickel(II) {[Ni(L)(H2O)2][Ni(pdc)2] where L = 1,4,8,11-tetraazaundecane (C7H20N4) and pdc = the dianion of pyridine-2,6-dicarboxylic acid (C7H3NO42−)} consists of an [Ni(L)(H2O)2]2+ complex cation and a [Ni(pdc)2]2– anion. The metal ion in the cation is coordinated by the four N atoms of the tetraamine ligand and the mutually trans O atoms of the water molecules in a tetragonally elongated octahedral geometry with the average equatorial Ni—N bond length slightly shorter than the average axial Ni—O bond [2.087 (4) versus 2.128 (4) Å]. The ligand L adopts its energetically favored conformation with five-membered and six-membered chelate rings in gauche and chair conformations, respectively. In the complex anion, the NiII ion is coordinated by the two tridentate pdc2– ligands via their carboxylate and nitrogen atom donors in a distorted octahedral trans-NiO4N2 geometry with nearly orthogonal orientation of the planes defining the carboxylate rings and the average Ni—N bond length [1.965 (4) Å] shorter than the average Ni—O bond distance [2.113 (7) Å]. In the crystal, the NH donor groups of the tetraamine, the carboxylic groups of the pdc2– anion and the coordinated water molecules are involved in numerous N—H...O and O—H...O hydrogen bonds, leading to electroneutral sheets oriented parallel to the (001) plane.